The Potential of Power Fluidics for Plant Protection - J. Grant; V. C. Marshall (Measurement + Control, 1977)
The possibility of using Direct Flow Control (DFC) to avoid catastrophic accidents due to containment breaches in chemical plant is discussed. Recommendations are made for locating fluidic elements, and the effectiveness of simple DFC protection is analysed. More powerful methods of protection are outlined using spin diversion, and the complementary properties of fluidic and conventional valves are exploited.